The Effectiveness of a Program Based on Media Education in Developing Positive Social Behavior in Kindergarten “Asemi-exprimental Study in Tartous City” - بركات , غسان; ديوب, هبة (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research aimed at measuring the effect of exposure to a training program on media education in developing some forms of positive social behavior consisting of compassion, cooperation and assistance. To achieve this purpose, the semi-experimental approach and the pre and post measurement were used and a program consisting of (18) sessions was designed. In addition, a positive social behavior scale consisting of (18) situations was prepared, and the reliability and consistency of it was confirmed. Both the program and the scale were introduced to a sample of (20) female and male first graders at a kindergarten in Tartous City. The results showed that there are statically significant differences between the pre and post measurement in favor of the post measurement, this proves the efficiency and positive effect of this program in developing some forms of the positive social behavior of the students who participated in it. The activation of media education programs at schools and allocating classes to teach them was suggested.